A novel mitochondrial orf147 causes cytoplasmic male sterility in pigeonpea by modulating aberrant anther dehiscence - Pooja Bhatnagar-Mathur; Ranadheer Gupta; Palakolanu Sudhakar Reddy; Bommineni Pradeep Reddy; Dumbala Srinivas Reddy; C. V. Sameerkumar; Rachit Kumar Saxena; Kiran K. Sharma (Plant Molecular Biology, 2018)

Mitochondrial SSRs and their utility in distinguishing wild species, CMS lines and maintainer lines in pigeonpea (Cajanus cajan L.) - Pawan Khera; Rachit Saxena; C. V. Sameerkumar; Kulbhushan Saxena; Rajeev K. Varshney (Euphytica, 2015)
Analysis of the pigeonpea mitochondrial genome sequence identified 25 SSRs. Mononucleotide SSR motifs were the most abundant repeats followed by dinucleotide and trinucleotide repeats. Primer pairs could be designed for 24 SSRs, 23 of which were polymorphic amongst the 22 genotypes consisting of cytoplasmic male sterile (CMS or A) line, maintainer or B line and wild Cajanus species representing six different CMS systems viz., A 1 , A 2 , A 4 , A 5 , A 6 and A 8 . These markers amplified a total of 107 alleles ranging from 2 to 10 with an average of 4.65 alleles per locus. The polymorphic information content for these markers ranged from 0.09 to 0.84 with an average of 0.52 per marker. Hence, the present study adds a novel set of 24 mitochondrial SSR markers to the markers repository in pigeonpea, which would be useful to distinguish the genotypes based on mitochondrial genome types in evolutionary and phylogenetic studies.